Impact of adding metal nanoparticles on anaerobic digestion performance – A review. (November 2019) - Lee, Yu-Jen; Lee, Duu-Jong
Graphical abstract: Highlights: Effects of metal NPs on AD performances were reviewed. Cytotoxicity of NPs to living organisms and environments were highlighted. Mechanisms for enhancement in AD performance with metal NPs were discussed. Research needs for or better design and control of the "NP strategy" was addressed. Abstract: Anaerobic digestion is the most widely adopted biological waste treatment processes with renewable energy production. The effects of adding metal nanoparticles (NPs) on improving digestion performance are well noted. This paper reviewed the traditional view on the cytotoxicity of NPs to living organisms and the contemporary view of mechanisms for enhancement in anaerobic digestion performance in the presence of metal NPs. The complicated interactions acquire further studies for comprehending the physical and chemical interactions of metal NPs to the constituent compounds and to the living cells, and the involvement of mechanisms such as direct interspecies electron transfer for better design and control of the "NP strategy" for anaerobic digestion performance enhancement.